Friend or Foe? Foreign investors and the liquidity of six Asian markets (2010)
Studying Foreign flows and the liquidity of six Asian markets we provide evidence of two empirical regularities: On the one hand, foreign trade has a negative but transitory impact on the overall liquidity of the market on a daily basis. This finding is shown consistent with two hypotheses: that foreign investors demand liquidity more aggressively than locals, and, to a lesser extent, that foreigners incorporate market-wide information. On the other hand, the overall share of foreign ownership in the market is positively related to improved liquidity, as shown in a sample of emerging markets, after controlling for a set of confounding factors. Overall, the results portray foreign investors as aggressive liquidity demanding, and nevertheless having a positive effect on the liquidity in short horizons